2014
DOI: 10.1021/jp507400n
|View full text |Cite
|
Sign up to set email alerts
|

Electron–Water Interactions and Implications for Liquid Cell Electron Microscopy

Abstract: Liquid cell electron microscopy enables direct in situ imaging of processes in liquids and objects suspended in liquids with nanoscale resolution. However, the irradiating electrons affect the chemistry of the suspending medium, typically an aqueous solution, producing molecular and radical products such as hydrogen, oxygen, and hydrated (solvated) electrons. These may impact the imaged structures and phenomena. A good understanding of the interactions between the electrons and the irradiated medium is necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

41
932
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(975 citation statements)
references
References 43 publications
41
932
2
Order By: Relevance
“…To analyze the evolution of the growth rate after nucleation, we first evaluated the effects of the electron beam, which increases the temperature of the specimen (18) and generates chemical species (19), on our system. We observed the growth of orthorhombic lysozyme crystals under different electron fluxes ( Fig.…”
Section: Significancementioning
confidence: 99%
“…To analyze the evolution of the growth rate after nucleation, we first evaluated the effects of the electron beam, which increases the temperature of the specimen (18) and generates chemical species (19), on our system. We observed the growth of orthorhombic lysozyme crystals under different electron fluxes ( Fig.…”
Section: Significancementioning
confidence: 99%
“…18,21,22,27,28 However, recent experimental observations have shown that these effects can be quantified, controlled and mitigated using calibrated electron doses. [28][29][30] As a result, in situ TEM observations can be used as an accurate starting point for understanding nanoparticle behavior in liquids.…”
mentioning
confidence: 99%
“…In addition, for the specific case of aqueous corrosion studies, the electron beam that is used as the imaging probe has two principle detrimental effects: first, it may charge the sample through direct electron transfer, which could lead to a change in the temperature of the solution and/or sample (Cazaux, 1995;Zheng et al, 2009); second, the beam may stimulate radiolysis in the electrolyte subtly changing its chemistry. These can change the pH and, together with temperature, can accelerate the electrochemical reaction at the Helmholtz double layer in the system (Schneider et al, 2014).…”
Section: In Situ Aqueous Studies: Corrosion Basicsmentioning
confidence: 99%